Reflective Journal as a Self-Directed and Sustainable Professional Development Tool for Pre-Service Teachers: A Case Study in English Language Education Study Program - Atalya Agustin (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2019)
Teaching practice is one among many programs in teachers training which focuses on having a professional preparation for work. In this program, student-teachers are asked to improve their skills through teaching actual students and engaging with school environment. Moreover, they are also building their own knowledge based on the improved teaching and learning process. It is crucial for them as pre-service teachers to encounter such experience. This meaningful theory and experience-based insights are possible to obtain if the student-teachers possess the commitment of self-reflection. There is likely a big chance that this action will be perpetual because of this personal initiative. This study aims to analyze the use of reflective journal as pre-service teachers’ professional development tool, their attitude towards reflective journal, as well as the strength and challenges arise related to the use of reflective journal during their teaching practice. The type of the research is a qualitative case study research. The data collection techniques being used are questionnaire and Focus Group Discussion (FGD). Moreover, the technique of analyzing the data was Miles and Huberman concept of data reduction, data presentation, and conclusion drawing. The results of this research will be presented in a descriptive-narrative manner by describing and discussing the data of the research.